Propuesta del sistema de gestión de la seguridad y salud en el trabajo en la empresa Eslingas de Colombia S.A.S., de conformidad con el marco normativo colombiano. (2021)
This work consists of a proposal of the System of Management of Safety and Health at Work in the company Eslingas de Colombia S.A.S. Initially raises the problem that the company has by not owning the aforementioned system, defines the objectives to be achieved in the project, details the methodology to be used to achieve the objectives raised and defines the theories required for this purpose. This methodology begins with the initial occupational safety and health assessment, firstly, the production, administrative, sourcing and dispatch processes were inspected, achieving the formats of safe work analysis in each of them, being these, a fundamental input for hazard identification, risk assessment and assessment.